“We Should Keep Fighting”: How Beliefs About Collective Action Success and Social Identity Process Fuel Future Activism - Mashuri, Ali; Zaduqisti, Esti; Nurmala, Sukma (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
The significance of social-psychological factors in reinforcing activism over time has been highlighted within collective action research. Against this backdrop, this research investigated the relationships among moral conviction, perceived intergroup threats, variables specified within the Social Identity Model of Collective Action (SIMCA; van Zomeren et al., 2008; i.e., politicized identification, perceived injustice, collective efficacy), internal attribution of collective action success, and people’s willingness to engage in future collective action. To this end, we recruited a sample of 410 Indonesian participants through a correlational survey. Data were analyzed using a path model, and the results revealed that such an internal attribution was a positive predictor of future collective action and mediated the effects of the SIMCA variables on it. The subsequent findings revealed the roles of moral conviction and perceived intergroup threats in explaining the SIMCA variables, implying that ethical commitment and perceived threats contribute to heightened politicized identification, perceptions of injustice, and collective efficacy. These findings provide empirical support for the relevance of multi-level modes of people’s willingness to engage in future collective action, highlighting the crucial roles of the internal and external driving factors.